Use of alcohol and other drugs among male university students and its meanings - Eliza Maria Rezende Dázio; Márcia Maria Fontão Zago; Silvana Maria Coelho Leite Fava
Abstract OBJECTIVE To understand the meanings that male university students assign to the condition of users of alcohol and other drugs. METHOD An exploratory study using a qualitative approach, with inductive analysis of the content of semi-structured interviews applied to 20 male university students from a public university in the southeast region of Brazil, grounded on the theoretical-methodological referential of interpretive anthropology and ethnographic method. RESULTS Data were construed using content inductive analysis for two topics: use of alcohol and/or drugs as an outlet; and use of alcohol and/or other drugs: an alternative for belonging and identity. CONCLUSION Male university students share the rules of their sociocultural environment that values the use of alcohol and/or other drugs as a way of dealing with the demands and stress ensuing from the everyday university life, and to build identity and belong to this social context, reinforcing the influence of culture.